ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI VOLUME IMPOR KEDELAI DI INDONESIA - Sinta Rahayu, (2024)
Indonesia is one of the largest soybean importers in the world. Most households consume soybean because it is more affordable than animal protein commodities. The demand for soybean consumption in Indonesia has increased along with the increase in population every year, but at the same time domestic production is not able to meet the high consumption needs. The continuing increase in the need for soybean consumption has resulted in the government importing it from soybean exporting countries in the world such as the United States, Canada, Brazil and Argentina. This research aims to determine and analyze the influence of soybean production, international soybean prices, rupiah exchange rate, and GDP per capita on the volume of soybean imports. The data in this research uses secondary data obtained through the official websites of the World Bank and the Ministry of Agriculture. This research uses quantitative data on Indonesian time series data from 1990-2021. This research uses a multiple linear regression method with the program used, namely Eviews 12. The results of this research show that (1) Soybean production has no influence on the volume of soybean imports. (2) The international price of soybeans has a significant negative effect on the volume of soybean imports. (3) The rupiah exchange rate has no influence on the volume of soybean imports. (4) Indonesia's GDP per capita has a significant positive effect on the volume of soybean imports. Simultaneously, soybean production, the international price of soybeans, the rupiah exchange rate against the US$ and Indonesia's GDP per capita influence the volume of soybean imports in Indonesia.